Digital Transformation and Batik Design Innovation: Improving the Quality and Market Expansion of MSME Borobudur Batik Houses - Nugroho Heri Cahyono; Insanul Qisti Barriyah; Deddy Setyawan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The challenges faced by the MSMEs of the Borobudur Batik House, which produce distinctive batik with motifs inspired by the reliefs of Borobudur Temple. Despite having great potential, these MSMEs face problems related to lack of design innovation, suboptimal production quality, and limited marketing to traditional methods. The purpose of this research is to develop batik design innovations, improve product quality, and introduce digital-based marketing strategies to expand market reach. The method used in this study is a community empowerment approach that involves training, mentoring, and the application of technology. The training was carried out in the form of workshops on contemporary batik design, environmentally friendly coloring techniques, and the use of digital marketing through social media and e-commerce. The results of the study show that after the training, Borobudur Batik House MSMEs succeeded in producing more innovative batik designs, improving product quality, and optimizing product marketing through digital platforms. The implication of this research is that the development of culture- and technology-based MSMEs can be a model of sustainable empowerment.